2011
DOI: 10.1159/000330269
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Double-Blind 2-Week Comparison Study of Azelastine Nasal Spray 0.1% versus Levocabastine Nasal Spray 0.05% in Patients with Moderate-to-Severe Allergic Rhinitis

Abstract: Objective: To compare the onset of action, efficacy, and safety of azelastine and levocabastine in the treatment of allergic rhinitis. Subjects and Methods: In a multicenter, randomized, double-blind, parallel-group trial, 244 patients with moderate-to-severe allergic rhinitis were randomized to receive either azelastine hydrochloride nasal spray (ANS) 0.1% or levocabastine hydrochloride nasal spray (LNS) 0.05% for 14 consecutive days. A visual analog scale was used to record total nasal symptom score (TNSS) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Currently, only 4 intranasal antihistamine products (AZEP, MIN QI, LIVOSTIN and SHUNTUOMIN) are available for the treatment of AR patients in China, of which AZEP (azelastine hydrochloride) has the largest share of the Chinese market ( Table 8 ). In a multicenter, randomized, double-blind, parallel-group trial, Han and colleagues 352 have demonstrated that azelastine and levocabastine nasal sprays, which are commonly used worldwide for the treatment of AR, are comparably safe and effective in the treatment of Chinese patients with moderate-to-severe persistent AR.…”
Section: Treatmentmentioning
confidence: 99%
“…Currently, only 4 intranasal antihistamine products (AZEP, MIN QI, LIVOSTIN and SHUNTUOMIN) are available for the treatment of AR patients in China, of which AZEP (azelastine hydrochloride) has the largest share of the Chinese market ( Table 8 ). In a multicenter, randomized, double-blind, parallel-group trial, Han and colleagues 352 have demonstrated that azelastine and levocabastine nasal sprays, which are commonly used worldwide for the treatment of AR, are comparably safe and effective in the treatment of Chinese patients with moderate-to-severe persistent AR.…”
Section: Treatmentmentioning
confidence: 99%
“…This included 24 studies with an active treatment comparator arm 1479,1805–1827 and 29 studies with an inactive placebo arm 1808,1809,1812–1814,1816,1818,1820,1822,1824,1825,1828–1845 . Monotherapy with azelastine was reported in 37 studies 1479,1805,1806,1808,1810–1816,1818–1828,1831–1836,1840–1848 while monotherapy with olopatadine was reported in 10 studies 1807,1809,1829,1830,1833,1835,1837–1839,1847 . Some studies utilized multiple active treatment arms of antihistamine and/or corticosteroid (Table XI.B.1.c).…”
Section: Managementmentioning
confidence: 99%
“…Azelastine and olopatadine were directly compared in three studies, with no significant difference in symptom relief between agents 1833,1835,1847 . Azelastine was compared with an experimental formulation of intranasal levocabastine in two additional studies, with either comparable or superior results for azelastine 1846,1848 . Levocabastine is not available as a commercial product.…”
Section: Managementmentioning
confidence: 99%